1972
DOI: 10.1042/bj1300363
|View full text |Cite
|
Sign up to set email alerts
|

The formation of cholest-5-ene-3β,26-diol as an intermediate in the conversion of cholesterol into bile acids by liver mitochondria

Abstract: 1. When [(14)C]cholesterol was incubated with rat liver mitochondria, radioactive 26-hydroxycholesterol, 3beta-hydroxychol-5-enoic acid and other bile acids were isolated from the incubation mixture. 2. In the absence of added 26-hydroxycholesterol, the specific radioactivity of the 26-hydroxycholesterol formed from [(14)C]cholesterol during the incubation was higher than that of the 3beta-hydroxychol-5-enoic acid. Addition of increasing amounts of 26-hydroxycholesterol led to a progressive fall in the specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1973
1973
1995
1995

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…An alternative explanation for changes in the relative proportions of cholic acid and chenodeoxycholic or ,-muricholic acids can be the existence of another pathway in the formation of bile acids, in addition to the major pathway involving initial 7a-hydroxylation of cholesterol [10,30], as has been suggested by several investigators to occur in the rat, hamster, rabbit and man [11][12][13][14][15]31]. This route may involve initial 26-hydroxylation of cholesterol by mitochondria, leading predominantly to the formation of chenodeoxycholic acid and /3-muricholic acid [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An alternative explanation for changes in the relative proportions of cholic acid and chenodeoxycholic or ,-muricholic acids can be the existence of another pathway in the formation of bile acids, in addition to the major pathway involving initial 7a-hydroxylation of cholesterol [10,30], as has been suggested by several investigators to occur in the rat, hamster, rabbit and man [11][12][13][14][15]31]. This route may involve initial 26-hydroxylation of cholesterol by mitochondria, leading predominantly to the formation of chenodeoxycholic acid and /3-muricholic acid [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…This route may involve initial 26-hydroxylation of cholesterol by mitochondria, leading predominantly to the formation of chenodeoxycholic acid and /3-muricholic acid [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an alternative pathway may exist, specifically in the formation of chenodeoxycholic acid. Human and rat liver mitochondria are able to convert cholesterol into 27-hydroxycholesterol [2,3]. It has been shown that this intermediate can be further metabolized to 3,J-hydroxy-5-cholenoic acid in rat liver peroxisomes [4] and to 7a-hydroxy intermediates by human liver microsomes and mitochondria [5,6], ultimately leading to preferential formation of chenodeoxycholic acid in rat and man [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a unique electron transfer system involving a "cytochrome P-450"-like entity in liver mitochondria would be of profound physiological significance. Since C-25 hydroxylase system for the side chain of vitamin D, [32] and C-26 one for that of cholesterol [33] have also recently been reported in liver mitochondria, it seems probable that a similar mechanism is potentially functioning in liver mitochondria for other metabolites.…”
Section: Electron Transfer and Comparative Viewmentioning
confidence: 99%